Analisis Pengaruh Perubahan Penghasilan Tidak Kena Pajak Terhadap Realisasi Penerimaan Pajak di Kantor Pelayanan Pajak Pratama Watampone - Syahrul HM; Abdul Rahim (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2018)
This research discusses the taxation problem in Kab. Bone, namely the problem of Non-Taxable Income (PTKP). The non-taxable income is the income limit is determined by the Ministry of Finance that has been approved by the People's Representative Council. PTKP is responsible for the number of people who are not taxable as a result of reduced income tax services, so this research will be carried out using Quantitative methods using an elasticity analysis tool to measure the sensitivity of its effect. The results of the study show that the Non-Taxable Income (PTKP), which is related to tax receipts from the Office of tax revenue, considering the data obtained from the pratama Watampone has shown that the proceeds at the time of tax (PPh 21), will ask in terms of community welfare, this is good news that the increase in PTKP gives the participation of small people not titled to tax. And it turns out the results of the analysis say that the PTKP is not too significant.